2000
DOI: 10.1210/jcem.85.2.6372
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Adrenal Incidentaloma in Italy1

Abstract: The aim of this study was to perform a national survey on occasionally discovered adrenal masses [adrenal incidentalomas (AI)] under the auspices of the Italian Society of Endocrinology. This multicentric and retrospective evaluation of patients with AI includes 1096 cases collected in 26 centers between 1980 and 1995. Relevant information was obtained by means of a specifically tailored questionnaire. Of the 1096 forms received, 1004 were retained for final analysis. Patients were 420 males and 584 females, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
109
3
32

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(162 citation statements)
references
References 26 publications
18
109
3
32
Order By: Relevance
“…In the study group, nearly 5% of the patients were diagnosed with adrenal carcinoma or adrenal metastasis from extraadrenal tissues, whereas another 5% of the patients had pheochromocytoma. Our findings are in line with the data of the previous studies that reported on the etiology of adrenal incidentalomas (10,11).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the study group, nearly 5% of the patients were diagnosed with adrenal carcinoma or adrenal metastasis from extraadrenal tissues, whereas another 5% of the patients had pheochromocytoma. Our findings are in line with the data of the previous studies that reported on the etiology of adrenal incidentalomas (10,11).…”
Section: Discussionsupporting
confidence: 93%
“…As has previously been reported, SCS is the most common functional abnormality among patients with adrenal incidentalomas (10,23), which was also found in 11.3% of our study population. Several observational studies reported that subtle cortisol excess in SCS is associated with increased cardiovascular risk (24,25).…”
Section: Discussionsupporting
confidence: 87%
“…Autopsy studies suggest a prevalence of clinically unapparent adrenal masses of around 2% (range 1.0-8.7%), which increases with age (5, 6, 7). Radiological studies report a frequency of around 3% in the age of 50 years, which increases up to 10% in the elderly (2,5,6,7,14,15,16). In childhood, adrenal incidentalomas are extremely rare.…”
mentioning
confidence: 99%
“…Описаны протекающие с классическими гипертензивными кризами "ФХЦ", которые оказываются гормонально неактивными аде-номами коры надпочечника или, что гораздо хуже, АКР [8,21].…”
Section: эпидемиологияunclassified
“…Основным критерием при формирова-нии показаний к операции долгое время являл ся размер новообразования, что при-водило, с одной стороны, к большому числу необоснованных вмешательств при опухолях более 3-4 см, с другой стороны, к недооцен-ке злокачественного потенциала образова-ний малого размера при метастатических поражениях и АКР. При изучении итальянско-го регистра [21] лишь 25% опухолей надпо-чечников более 4 см оказались злокаче-ственными. Одновременно авторы привели данные, что среди больных АКР опухоли менее 6 см составляли около 10% наблюде-ний; с другой стороны, среди всех опухолей надпочечника более 6 см в диаметре АКР соста вил только 20% (!).…”
Section: в качестве метода первичной диагно-unclassified